2012
DOI: 10.3109/14767058.2012.743524
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length and risk of antepartum hemorrhage in presence of low-lying placenta

Abstract: In women with low-lying placenta persisting into third trimester, short cervical length can be used as a predictor for APB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Twenty-five retrospective and four prospective cohort studies involving a total of 4687 individuals were included in the study (Table 1). Fourteen1516171819202122232425262728 took place in Asia, eight529303132333435 in North America, six101136373839 in Europe, and one40 in Africa. The articles were published between 1985 and 2016, and the median number of participants per study was 162 (range, 40–703).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five retrospective and four prospective cohort studies involving a total of 4687 individuals were included in the study (Table 1). Fourteen1516171819202122232425262728 took place in Asia, eight529303132333435 in North America, six101136373839 in Europe, and one40 in Africa. The articles were published between 1985 and 2016, and the median number of participants per study was 162 (range, 40–703).…”
Section: Resultsmentioning
confidence: 99%
“…The major causes of APH are placenta previa and abruption placenta. Other risk factors include marginal sinus bleeding, vasa previa, cord velamentous insertion, battledore placenta, cervicitis, genital trauma, tumours, infections, and coagulation defects203042.…”
Section: Discussionmentioning
confidence: 99%
“…On transvaginal sonography at 28 to 33 weeks, the best cervical length cutoff for the identification of women at high risk for emergency cesarean delivery is 31 mm or less (16 times higher risk of preterm cesarean delivery with 83.3% sensitivity and 76.6% sensitivity) . Using a similar cervical length cutoff, others authors found that women presenting with placenta previa with a cervical length of 30 mm or less in 3 studies and 25 mm or less in 2 studies had higher rates of antepartum bleeding requiring emergency delivery. In our study, we found that the rate of cervical length shortening for the identification of women at high risk for emergency cesarean delivery was greater than 0.7 mm/wk (with 86.7% sensitivity, 53.8% specificity, 68.4% positive predictive value, and 77.8% negative predictive value).…”
Section: Discussionmentioning
confidence: 99%
“…Low-lying placenta is diagnosed when the distance between the internal cervical os and the placental edge is 1-20 mm. [9][10][11][12][13][14]22,23 If the distance between the internal cervical os and the placental edge is >20 mm, the patients should be managed as per routine because the overwhelming majority of studies have not demonstrated an increased risk for cesarean delivery due to hemorrhage. [9][10][11][12][13] Due to the normal process of "placental migration" as the lower uterine segment matures, the ultrasound examination may be repeated in the third trimester to identify those patients who can be allowed to go to term vs those who are at increased risk for antepartum hemorrhage and preterm delivery, and therefore need to be carefully watched.…”
Section: Marginal/low-lying Placentamentioning
confidence: 98%
“…10,[12][13][14] It was found that short cervix ( 25 mm) was associated with higher rates of antepartum bleeding (75% vs 31%; P ¼ .02), blood transfusion (25% vs 3%; P ¼ .02), lower birthweight (62% vs 17%; P ¼ .02), and neonatal intensive care unit admissions (50% vs 17%; P ¼ .04). 22 Figure 3 is a proposed guideline for managing asymptomatic patients with marginal or low-lying placenta based on published literature that has used internal cervical os to placental edge distance cutoffs of <1, 1-2, and >2 cm; placental edge thickness cutoff of 1 cm; and cervical length cutoff of 25 mm. This guideline may be used as alternative to the current recommendations of preterm delivery at a predetermined gestational age.…”
Section: Marginal/low-lying Placentamentioning
confidence: 99%